Age-Related Hearing Loss and the Development of Cognitive Impairment and Late-Life Depression: A Scoping Overview - Sharma, Rahul K.; Chern, Alexander; Golub, Justin S. (Seminars in Hearing, 2021)
Age-related hearing loss (ARHL) has been connected to both cognitive decline and late-life depression. Several mechanisms have been offered to explain both individual links. Causal and common mechanisms have been theorized for the relationship between ARHL and impaired cognition, including dementia. The causal mechanisms include increased cognitive load, social isolation, and structural brain changes. Common mechanisms include neurovascular disease as well as other known or as-yet undiscovered neuropathologic processes. Behavioral mechanisms have been used to explain the potentially causal association of ARHL with depression. Behavioral mechanisms include social isolation, loneliness, as well as decreased mobility and impairments of activities of daily living, all of which can increase the risk of depression. The mechanisms underlying the associations between hearing loss and impaired cognition, as well as hearing loss and depression, are likely not mutually exclusive. ARHL may contribute to both impaired cognition and depression through overlapping mechanisms. Furthermore, ARHL may contribute to impaired cognition which may, in turn, contribute to depression. Because ARHL is highly prevalent and greatly undertreated, targeting this condition is an appealing and potentially influential strategy to reduce the risk of developing two potentially devastating diseases of later life. However, further studies are necessary to elucidate the mechanistic relationship between ARHL, depression, and impaired cognition.
Keywords: presbycusis; age-related hearing loss; depression; dementia; cognitive decline